UMA MICROPOLÍTICA DO CUIDADO E A PSICOSSOMA-ATIVIDADE: AS PRÁTICAS DO PSICÓLOGO COM O CORPO E A ACUPUNTURA - Pereira, Eduardo Luiz Hubner (2021)
How do psychology and acupuncture become related in the Brazilian context? Which theoretical, epistemological, technical, and ethical-political issues can show up in this scenery? Where is psychology positioned and how does it claim its care promotion role and body-subjectiveness? Which other questions can emerge on this subject? This cartographic research focuses on tracing the possible activities that can be performed on the body by the psychologist, using the health and care promotion tools that are available when meeting acupuncture. In the boundaries of this subject, which has psychology representing the scientific knowledge on one side, and on the other one, the millenary acupuncture techniques representing the traditional and popular knowledge, I managed to map where and how they merge and stand out from each other, the effects they develop, and the new connections that arise when acupuncture meets psychology care and clinical fields. To that end, I used the concepts of Institutional Analysis and Schizoanalysis of the Analysis of Implication, the Analyst, Instituting and Instituted, the War Machine, Body without Organs, transversality and transdisciplinarity. For that matter, theoretical debates were built around the relationship between medicine, psychology and acupuncture, medical psychology, psychosomatics, and the proposal of the psychosoma-activity concept, as a way of connecting these ideas together, as they are related to the subjects studied on the meetings and interviews with acupuncture psychologists during the research. Among the findings of this cartographic research, there are a history of political issues faced by pioneer adopters of this practice, the ethical-political clash between psychology and acupuncture, its abyssal fissures and bindings with biopolitics and biopower, as well as the beauty of this merge that encourages today’s psychology to be in tune with humane health and care principles, clearing the path for a more present cross care micropolicy.